2023
DOI: 10.1212/nxi.0000000000200096
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effects of Domain-Specific Human Monoclonal Antibodies Against LGI1 on Neuronal Excitability

Abstract: Background and ObjectivesAutoantibodies to leucine-rich glioma inactivated protein 1 (LGI1) cause an autoimmune limbic encephalitis with frequent focal seizures and anterograde memory dysfunction. LGI1 is a neuronal secreted linker protein with 2 functional domains: the leucine-rich repeat (LRR) and epitempin (EPTP) regions. LGI1 autoantibodies are known to interfere with presynaptic function and neuronal excitability; however, their epitope-specific mechanisms are incompletely understood.MethodsWe used patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…31 In contrast, some studies observed an increased neuronal excitability only with LRR but not with EPTP autoantibodies. 31,57,58 Our data indicate that the duration of the action potential is preferentially affected by EPTP autoantibodies, whereas LRR-targeting antibodies were previously shown to interfere with multimerization and cause internalization of the LGI1-ADAM22 complex. 13,30,31 A differential effect of autoantibodies targeting EPTP and LRR is conceivable because of the complex interplay of various types of potassium channels in controlling excitability and action potential repolarization.…”
Section: Monoclonal Autoantibodies Targeting the Eptp-domain Of Lgi1 ...mentioning
confidence: 68%
See 2 more Smart Citations
“…31 In contrast, some studies observed an increased neuronal excitability only with LRR but not with EPTP autoantibodies. 31,57,58 Our data indicate that the duration of the action potential is preferentially affected by EPTP autoantibodies, whereas LRR-targeting antibodies were previously shown to interfere with multimerization and cause internalization of the LGI1-ADAM22 complex. 13,30,31 A differential effect of autoantibodies targeting EPTP and LRR is conceivable because of the complex interplay of various types of potassium channels in controlling excitability and action potential repolarization.…”
Section: Monoclonal Autoantibodies Targeting the Eptp-domain Of Lgi1 ...mentioning
confidence: 68%
“…Indeed, it was recently shown that LGI1 autoantibodies also alter the Kv1 cluster distribution at the axon initial segment. 57,58 The autoantibody-induced increase in neuronal excitability was mediated by antibodies specifically targeting the LRR-domain. 30,31,57,58 Consistently, structural analyses indicate that LGI1 can form protein complexes in a cis-configuration serving as an extracellular scaffold instead of a transsynaptic hub.…”
Section: Presynaptic Functions Of Lgi1 Outside Of the Release Sitementioning
confidence: 99%
See 1 more Smart Citation
“… 10 In vitro primary neuronal cultures also incubated for 7 days with LRR- and EPTP-specific mAbs showed that LRR-directed mAbs could directly affect neuronal excitability, but this effect was less pronounced in EPTP-specific mAb exposed neurons. 23 In contrast to the action of LRR mAbs in vitro , the EPTP mAbs are reported to exert their effects by directly inhibiting the docking of LGI1 to the ADAM proteins. 14 In our study, EEG recordings have demonstrated increases in network and neuronal excitability in hippocampal CA3 in vivo by both LRR and EPTP domain directed LGI1 autoantibodies.…”
Section: Discussionmentioning
confidence: 99%
“… 14 In our study, EEG recordings have demonstrated increases in network and neuronal excitability in hippocampal CA3 in vivo by both LRR and EPTP domain directed LGI1 autoantibodies. 10 , 23 Studies have shown that LRR- and EPTP-specific antibodies co-occur in patients with LGI1-antibody encephalitis but the numbers of recorded rats with either mAb subclass do not allow for statistical comparison of epitope-specific clinical features ( Supplementary Fig. 1 ).…”
Section: Discussionmentioning
confidence: 99%